Arrested Development? An Empirical Analysis of Education Choices and Migration Intentions - Mendoza, Ronald U (Archīum Ateneo, 2013)
An estimated 10% of the Philippine population — about 10 million people — is overseas. While they contribute significantly to the Philippine economy by way of remittances and other connections, there may be a growing risk of brain and skills drain that could be detrimental to the country’s long run growth prospects. In crafting any possible response, it would be critical to understand the motivations of the Filipino youth, who comprise a large share of the migrant population, and notably since the country is on the cusp of a youth bulge. In order to contribute to the evidence-base in this area, this study turns to a unique survey of about 2500 Philippine college students, empirically examining the factors that influence youth migration intentions. It identifies and evaluates the strength of the various push and pull factors that might ultimately determine the decision to migrate. The study finds that a student who has relatives and friends abroad who encourage migration as well as relatives and friends in the Philippines who encourage migration is 11.75 times more likely to have an intention to migrate compared to the baseline student. A student who witnessed cheating in local elections is 1.35 times more likely to have an intention to migrate compared to the baseline student. The results of the study highlight the potentially increasing challenges for policymakers who seek to facilitate a better match between young people’s skills and job opportunities at home. Regional integration, such as the imminent emergence of the ASEAN Economic Community in 2015, could accentuate these factors, further underscoring the importance of policies to address youth unemployment, underemployment, and education-job mismatches. While domestic policies will still be needed, international cooperation could prove increasingly critical.